EFFICIENCY OF ARBUSCULAR MYCORRHIZAL FUNGI AND SOME SPECIES OF PLANT GROWTH PROMOTING RHIZOBACTERIA TO CONTROL FUNGI Fusarium chlamydosporum CAUSING AGENT OF DECLINE DATE PALM OFF SHOOTS - & et al., Matloob (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The objective of this study was to evaluation the efficiency of Arbuscular mycorrhizal fungi and some species of Plant growth promoting rhizobacteria (PGPR) to control Fusarium chlamydosporum fungus causing agent of decline date palm off-shoots. The isolation and identification results showed presence of F. chlamydosporum fungus from infected roots of infected palm trees and its major causing agent of diseases. The results appeared Pseudomonas fluorescens , Azotobacter chroococcum and Azosperillium sp. have high antagonism of pathogen under laboratory conditions. The evaluation results of biocontrol factors Glomus intraradices, G. mosseae, Gigaspora, P. fluorescens, A. chroococcum and Azospirillum sp. indicated that all treatments caused significant reduction in disease severity of death palm off-shoots disease into13.3-60.0%. compared to control (pathogen only) 86.7%. The interaction between G. intraradices and P. flourescens caused significant reduction in disease severity to 13.3% and enhanced the growth of foliage and root of offshoots length to 39.0 and 36.3cm respectively and increased the fresh and dry weight of foliage and root, 1.7750, 0.4977, 1.764 and 0.339g this result was closed to Beltanol fungicide effect. Also all biocontrol agents which used in this study alone (without pathogen) enhancement of plant growth compared with control treatment. The results of the current study showed for the first time that Arbuscular mycorrhizal fungi and Azospirillum sp. Bactrium to control and have good inhibition of Fusarium chlamydosporum fungus causing agent of decline date palm off-shoots and increasing plant growth in Iraq.